Synthesis and reactions of halogenated stilbenes mediated by Lewis acid and QSAR studies of stilbene analogues / Mohd Fadzli Md Din - Mohd Fadzli , Md Din (2016)
A total of nine halogenated stilbenes have been produced by Heck coupling method. Five halogenated stilbenes were then subjected to cytotoxicity test on five cancer cell lines and one normal human cell lines. (E)-N-(2-(3-fluorostyryl)phenyl)acetamide 98 displayed good antiproliferative on some of the cancer cell lines. Moreover, all the stilbenes did not show any cytotoxicity on the normal human cell line. Investigation on Lewis acid reactions; FeCl3 and SnCl4, were pursued on the halogenated stilbenes and produced imines for the former and indolines for the latter. Products conceived from these reactions were discussed thoroughly. Quantitative structure activity relationship (QSAR) study was done on several stilbene analogues to relate the bioactivity of the estrogen- insensitive breast cancer line with the molecular structure of the stilbene analogues. Three types of QSAR applied on these stilbene analogues were 2D QSAR, 3D QSAR and 3D QSAR pharmacophore. 3D QSAR pharmacophore showed the most promising model in predicting activity of new ligands.